Learn SQL using MySQL in One Day and Learn It Well. - Jamie Chan; PACKT (GB: Packt, 2024)
Master SQL and unlock the power of database management. From basics to advanced queries, this book guides you through practical exercises to efficiently manage data. Key Features Step-by-step guidance from basic to advanced SQL techniques Comprehensive coverage of MySQL, a leading database management system Practical exercises with solutions to reinforce learning Book Description Learn SQL (using MySQL) in One Day and Learn It Well is the ultimate guide for beginners aiming to grasp the complexities of SQL through hands-on learning. Starting with an introduction to the essence of databases, this book methodically advances through defining and manipulating tables, mastering data insertion, updates, deletions, and executing sophisticated data selection techniques across its comprehensive chapters. It further explores the creation and utility of views, the implementation of triggers to automate database responses, and the intricacies of variables, stored routines, control flow tools, and cursors, culminating in a capstone project that brings all concepts together. Culminating in a project , this book offers a unique opportunity to apply all the learned concepts in a practical, real-world scenario, reinforcing the skills and knowledge acquired throughout the chapters. The appendices provide additional resources including table definitions for practical exercises modeled on real-world scenarios. Embark on a learning journey that transitions you from novice to proficient in managing and querying databases with MySQL, empowering you with the skills to tackle real-world data challenges. What you will learn Understand the fundamental concepts and architecture of databases Define and design efficient database tables to store data logically Utilize advanced selection techniques to manipulate & analyze data Create views to simplify complex queries and enhance accessibility Implement triggers to automate database operations Complete a hands-on project to apply skills in a practical scenario Who this book is for This book is ideal for individuals with no prior experience in SQL or database management. It is perfect for those looking to acquire a strong foundational understanding of SQL using MySQL. Pre-requisites include basic computer literacy and an eagerness to learn data management techniques.
Data in extended ASCII character set.
Mode of access: Internet.